Ответ:
Пошаговое объяснение:
8x = -62,4 + 5x
8x - 5x = -62,4
3x = -62,4
x = -62,4 : 3
x = -20,8
==========
0,6x + 4,2 = 0,5x - 1,5 + 6,8
0,6x + 4,2 = 0,5x + 5,3
0,6x - 0,5x = 5,3 - 4,2
0,1x = 1,1
x = 1,1 : 0,1
x = 11
I) 3(a+2b)-a, при а+3b=1,1. => a=1,1-3b => 3(1,1-3b+2b)-1,1-3b=3,3-3b-1,1-3b=2,2
II) 2,4(3x+5y)-4y, при 0,9x+y=2. => y=2-0,9x => 2,4(3x+5(2-0,9x))-4(2-0,9x)=2,4(3x+10-4,5x)-8+3,6x=7,2x+24-10,8x-8+3,6x=16
III)8(0.5a+3b)+8a, при а+2b=2,5. => a=2,5-2b => 8(0.5(2,5-2b)+3b)+8(2,5-2b)=8(1,25-b+3b)+20-16b=10-16b+20-16b=10
IV) 3(0,6m+5n)-3n, при 0,3m+2n=4 => n = (4-0,3m)/2=2-0,15m => 3(0,6m+5(2-0,15m))-3(2-0,15m)=3(0,6m+10-0,75m)-6+0,45m=30-0,45m-6+0,45m=24
p,s, Спасибо за задачу :)